Analysis of a Kind of Quitting Smoking Model with Beddington-DeAngelis Function (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we discuss the dynamics of quitting smoking withBeddington-DeAngelis function. Firstly, the basic reproduction number of themodel is obtained by establishing the basic reproduction matrix. Then, byusing the Routh-Hurwitz criterion and Lyapunov functionals and LaSalle'sInvariant Principle and the second additive compound matrix, local and globaldynamics of the model are analyzed. Based on the partial rank correlationcoefficients (PRCCs), we discuss some biological implications and focus onthe impact of some key model parameters. Finally, the numerical simulationsshow the theoretical analysis more intuitively, and we give some strategies tocontrol the spread of smokers.